Ways to Reduce the Impact of Cotton in the Separator Worker Chamber - Nurmukhammad Qizi, Salokhiddinova Makhliyo (International Journal of Psychosocial Rehabilitation, 2020)
The article describes the transfer of cotton to the next technological process while preserving its natural properties during the initial processing process. The analysis of ways to reduce shock forces during the removal of cotton seeds from the air was analyzed. For this purpose it is based on the first cotton processing of cotton.